2001
DOI: 10.1016/s0741-8329(01)00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances after acute exposure to alcohol in mothers’ milk

Abstract: The results of previous research in our laboratory revealed that breast-fed infants experience significantly less active sleep after exposure to alcohol in their mothers' milk than do breast-fed infants not exposed to alcohol. The present study tested the hypothesis that infants would compensate for such reductions if their mothers then refrained from drinking alcohol. To this end, 23 breast-fed infants from 3 to 5 months of age and their mothers were tested on 2 days separated by 1 week. A small, computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
0
41
0
2
Order By: Relevance
“…45 During the first half of the centre 3.5-hour testing session there was no significant difference in the amount of time spent in active sleep. However, during the second half of this session (1.75-3.5 hours) infants exposed to alcohol in the mother' s milk spent less time in active sleep, compared with the control condition.…”
Section: Iii-2mentioning
confidence: 87%
See 2 more Smart Citations
“…45 During the first half of the centre 3.5-hour testing session there was no significant difference in the amount of time spent in active sleep. However, during the second half of this session (1.75-3.5 hours) infants exposed to alcohol in the mother' s milk spent less time in active sleep, compared with the control condition.…”
Section: Iii-2mentioning
confidence: 87%
“…7,38,45 The mechanism for this effect on sleep patterning remains to be explained; 7,38,45 however, Mennella and Gerrish 7 propose based on their results and that of others 43,46 slight deficit identified in the motor development of the children exposed to chronic alcohol intake may be a result of continued disruption of active sleep subsequent to regular alcohol intake (evidence level Ioffe and Chernick-NHMRC III-2). Animal model studies and experimental studies in humans suggest that pre-and postnatal experiences with the smell and taste of ethanol can affect later responsiveness to ethanol.…”
Section: Iii-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this science, it would seem that the recommendation for lactating women to drink a glass of beer or wine shortly before nursing may actually be counterproductive. While mothers may be more relaxed after a drink, their babies will ingest less milk (Mennella and Beauchamp) and infants'sleep will be disrupted in the short term (Mennella & Garcia-Gomez, 2001). Beyond alcohol's teratogenic effects on the fetus and disruptive effects on the lactational process, a growing body of experimental research in animal models suggests that during ethanol exposure, the fetus or young infant can acquire an association between ethanol's orosensory properties and pharmacological consequences, causing the animal subsequently to seek out ethanol Pepino, Abate, Spear, & Molina, 2002).…”
Section: Early Learning About the Sensory Properties Of Alcoholmentioning
confidence: 99%
“…17 Mothers also refrained from drinking any alcoholic beverages during the 3 days preceding each test day, because our previous research demonstrated alterations in sleep and activity levels after exposure to alcohol in mothers' milk. 16,18 Each mother-infant dyad arrived at the Monell Center at ~9:30 AM. Infants were last breastfed 2.5 ± 0.2 hours before testing; there was no significant difference in the time since the infants were last fed on the 2 testing days.…”
Section: Methodsmentioning
confidence: 99%